Phyto-oxylipin mediated plant immune response to colonization and infection in the soybean-Phytophthora sojae pathosystem - Adigun, Oludoyin Adeseun; Pham, Thu Huong; Grapov, Dmitry; Nadeem, Muhammad; Jewell, Linda Elizabeth; Cheema, Mumtaz; Galagedara, Lakshman; Thomas, Raymond (Frontiers in Plant Science, 2023)
Introduction Food security is a major challenge to sustainably supply food to meet the demands of the ever-growing global population. Crop loss due to pathogens is a major concern to overcoming this global food security challenge. Soybean root and stem rot caused by Phytophthora sojae results in approximately 20B $US crop loss annually. Phyto-oxylipins are metabolites biosynthesized in the plants by oxidative transformation of polyunsaturated fatty acids through an array of diverging metabolic pathways and play an important role in plant development and defense against pathogen colonization and infection. Lipid mediated plant immunity is a very attractive target for developing long term resistance in many plants’ disease pathosystem. However, little is known about the phyto-oxylipin’s role in the successful strategies used by tolerant soybean cultivar to mitigate Phytophthora sojae infection. Methods We used scanning electron microscopy to observe the alterations in root morphology and a targeted lipidomics approach using high resolution accurate mass tandem mass spectrometry to assess phyto-oxylipin anabolism at 48 h, 72 h and 96 h post infection. Results and discussion We observed the presence of biogenic crystals and reinforced epidermal walls in the tolerant cultivar suggesting a mechanism for disease tolerance when compared with susceptible cultivar. Similarly, the unequivocally unique biomarkers implicated in oxylipin mediated plant immunity [10(E),12(Z)-13S-hydroxy-9(Z),11(E),15(Z)-octadecatrienoic acid, (Z)-12,13-dihydroxyoctadec-9-enoic acid, (9Z,11E)-13-Oxo-9,11-octadecadienoic acid, 15(Z)-9-oxo-octadecatrienoic acid, 10(E),12(E)-9-hydroperoxyoctadeca-10,12-dienoic acid, 12-oxophytodienoic acid and (12Z,15Z)-9, 10-dihydroxyoctadeca-12,15-dienoic acid] generated from intact oxidized lipid precursors were upregulated in tolerant soybean cultivar while downregulated in infected susceptible cultivar relative to non-inoculated controls at 48 h, 72 h and 96 h post infection by Phytophthora sojae, suggesting that these molecules may be a critical component of the defense strategies used in tolerant cultivar against Phytophthora sojae infection. Interestingly, microbial originated oxylipins, 12S-hydroperoxy-5(Z),8(Z),10(E),14(Z)-eicosatetraenoic acid and (4Z,7Z,10Z,13Z)-15-[3-[(Z)-pent-2-enyl]oxiran-2-yl]pentadeca-4,7,10,13-tetraenoic acid were upregulated only in infected susceptible cultivar but downregulated in infected tolerant cultivar. These microbial originated oxylipins are capable of modulating plant immune response to enhance virulence. This study demonstrated novel evidence for phyto-oxylipin metabolism in soybean cultivars during pathogen colonization and infection using the Phytophthora sojae-soybean pathosystem. This evidence may have potential applications in further elucidation and resolution of the role of phyto-oxylipin anabolism in soybean tolerance to Phytophthora sojae colonization and infection.